2018
DOI: 10.1039/c8dt03741h
|View full text |Cite
|
Sign up to set email alerts
|

Two water-stable lanthanide metal–organic frameworks with oxygen-rich channels for fluorescence sensing of Fe(iii) ions in aqueous solution

Abstract: A strategy is proposed to construct oxygen-rich channel MOFs as chemosensors for sensing Fe3+ ions using oxygen-enriched multi-carboxylic acid ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(56 citation statements)
references
References 53 publications
6
47
0
3
Order By: Relevance
“…These interactions could reduce the electronic transitions within the complex and lead to luminescence quenching. Similar phenomena have been observed in some CPs with uncoordinated O atoms (Ding et al, 2017;Liu et al, 2018;Shang et al, 2018). As a consequence, the quenching effect may be related to both the energy competition and the weak interactions between the CPs and the sensing analytes.…”
Section: àsupporting
confidence: 74%
See 1 more Smart Citation
“…These interactions could reduce the electronic transitions within the complex and lead to luminescence quenching. Similar phenomena have been observed in some CPs with uncoordinated O atoms (Ding et al, 2017;Liu et al, 2018;Shang et al, 2018). As a consequence, the quenching effect may be related to both the energy competition and the weak interactions between the CPs and the sensing analytes.…”
Section: àsupporting
confidence: 74%
“…To the best of our knowledge, only two compounds have been reported to distinguish between Cr 2 O 7 2À and CrO 4 2À by luminescence. The first example of a 2D Eu-CP was reported by Liu et al (2018) and synthesized by the solvothermal reaction of an imidazoliumbased dicarboxylic acid ligand (Yang et al, 2018). The other was reported by our group very recently (Sheng et al, 2019).…”
Section: àmentioning
confidence: 99%
“…According to recent studies in fluorescence-based detection systems, this limit value was found to be low. [44][45][46][47] On the other hand, considering EPA, the limit value for Fe 3+ in drinking water has been reported to be 5.357 μM. 48 Remarkably, in this study, it was found that the determined LOD value for Fe 3+ (32.1 nM) was much lower than that allowed by the EPA and the sensitivity was much better.…”
Section: Detection Of Fe 3+ Ionsmentioning
confidence: 66%
“…Based on Figure 3(f), the LOD value for Fe 3+ was determined as 32.1 nM according to the 3 s/k system. According to recent studies in fluorescence‐based detection systems, this limit value was found to be low 44–47 . On the other hand, considering EPA, the limit value for Fe 3+ in drinking water has been reported to be 5.357 μM 48 .…”
Section: Detection Of Fe3+ Ionsmentioning
confidence: 99%
“…Asam (91) borat akan larut jika dilarutkan dengan air mendidih. (92)(93)(94)(95)(96) Namun, ketika dipanaskan (97) di atas 170 °C, asam borat akan kehilangan air, (98) membentuk HBO 2 atau yang dikenal dengan asam metaborat.…”
Section: Analisis Gapunclassified